Home-School Partnership: How do Indonesian elementary school principals perceive it? - YANTORO YANTORO; DIAN NISA ISTOFA (Universitas Jambi, Indonesia, 2020)
Home-school partnerships is defined as the collaboration between family and school and to improve students' achievement. Even though many empirical researches have been published in the area of educational management, important gaps in this study in regards toward the analysis in the developing countries including Indonesia. This study utilized interviews with Indonesian school principals in exploring their perspectives and practices of home-school partnership in Indonesian elementary education. The participants were six elementary school principals from six Indonesia elementary schools. The study informs that Indonesian elementary school principals have perceptions which are consistent towards the importance roles of home-school partnership. Besides, they inform the implementation of home-school partnership; however, a parent-teacher association is not established. The school principals involved in this study also informed that parents’ lack of knowledge and insufficient time as the two barriers from home-school relationship. Recommendation and suggestion are offered to tackle the barriers. The results of the study suggest the improvement of training for teachers to build communication with parents various backgrounds of culture and experiences are needed.